2023
DOI: 10.1055/a-2039-3388
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Head-to-Head Comparison of Three Clinical Models to Predict Occurrence of Postthrombotic Syndrome: A Validation Study

Abstract: Objective: The SOX-PTS, Amin, and Méan models are three different clinical prediction scores stratifying the risk for post-thrombotic syndrome (PTS) development in patients with acute deep vein thrombosis (DVT) of the lower limbs. Herein, we aimed to assess and compare these scores in the same cohort of patients. Methods: We retrospectively applied the three scores in a cohort of 181 patients (196 limbs) who participated in the SAVER pilot trial for an acute DVT. Patients were stratified into PTS-risk groups u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In terms of model performance, the discrimination of most prediction models was between 0.7 and 0.8, and the pooled discrimination of meta-analysis was 0.75, which was moderate accuracy. Michelle Pradier conducted a study to assess the performance of SOX-PTS score ( Anat Rabinovich,2018 [ 18 ]), Méan model ( Marie Méan, 2018 [ 19 ]) and Amin model ( Elham E. Amin, 2018 [ 20 ]) in SAVER database [ 27 ]. The result showed that, the performance of the SOX-PTS score and the Méan model were acceptable with an AUC of 0.72 and 0.74 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of model performance, the discrimination of most prediction models was between 0.7 and 0.8, and the pooled discrimination of meta-analysis was 0.75, which was moderate accuracy. Michelle Pradier conducted a study to assess the performance of SOX-PTS score ( Anat Rabinovich,2018 [ 18 ]), Méan model ( Marie Méan, 2018 [ 19 ]) and Amin model ( Elham E. Amin, 2018 [ 20 ]) in SAVER database [ 27 ]. The result showed that, the performance of the SOX-PTS score and the Méan model were acceptable with an AUC of 0.72 and 0.74 respectively.…”
Section: Discussionmentioning
confidence: 99%